Validation study of the Malay version of positive emotion and associated factors in patients with depression at the outpatient clinic of Hospital Bahagia Ulu Kinta (HBUK) / Fatihah Addawiyah Mohammed - Fatihah Addawiyah , Mohammed (2017)
The level and associated factors of Positive Emotion in patients with depression at the outpatient clinic of Hospital Bahagia Ulu Kinta (HBUK), Perak. Objective: Positive emotion is frequently being neglected in the management of depression. Positive emotion has an important role in relation to the depression. This is a cross-sectional study with objective to measure the level of positive emotion and to study associated factors of positive emotion among depressed patients. Method: A total of 104 depressed patients were recruited via convenient sampling from the outpatient clinic of HBUK from July 2016 to September 2016. Subjects were assessed with Malay version of Positive Emotion Rating Scale, Malay version of Center for Epidemiological Studies Depression, Malay version of Snaith-Hamilton Pleasure Scale, Malay version of Duke Religious Index, Malay version of Brief Religious Coping and questionnaire on relevant sociodemographic and clinical profile. Results: There were more depressed female (70.2%) than male (29.8%), with Chinese predominant (54.8%) than other races. Most of the depressed patients were married (63.5%), attained minimum level of secondary education (62.5%) and employed (55.8%). All of the depressed patients were on medication, with the majority were on Selective Serotonin Reuptake Inhibitors (SSRIs) antidepressant (77.9%). Despite being on medication, near half of the depressed patients still had ongoing depressive symptoms, lower hedonic capacity and lower positive emotion. There were no significant associated factors between positive emotion with sociodemographic and different types of medication, except one significant association with age. Depressed patients with age above 45 years old were found to have higher level of positive emotion than younger patients. There were significant associations between positive emotion with religiosity iii and positive religious coping. Depressed patients with higher level of positive emotion were found to have higher level of religiosity and positive religious coping. However, this study did not find significant association between positive emotion and negative religious coping. Conclusion: Positive emotion is significantly associated with depression. This study found that age, religiosity and positive religious coping significantly associated with positive emotion. Religion and religious coping could be helpful to enhance positive emotion and to reduce psychological distress in the depressed patients.